The role of metalinguistic function in the construction of physical knowledge: Α theatre semiotics approach for preschool education - PANAGIOTIS PANTIDOS (Metaichmio Publications, 2008)
The rendering of physical knowledge in typical or non typical forms of teaching, is a process in which the spoken word and the language in general that is used centre on the (pre-) scientific code. In the case of science teaching, the special pedagogic framework places the discussion on concepts - regardless of school grade - at a metalinguistic level of elaboration. At this level, the extent of learning, internalisation and use of the special code is intensely brought out through the utterances of the teachers and the students. In this paper an attempt is made, through semiotic theatrical analysis, to study the sign-vehicles that are related to the metalinguistic function of the speech in preschool education. Thus, the "commentary on the (pre-)scientific code" as well as the "means which project the metalinguistic function of the speech" are analysed within a context set up by the physical knowledge for preschool education based on the world of drama.